2014
DOI: 10.1002/mc.22246
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract targets mitochondrial electron transport chain complex III and induces oxidative and metabolic stress leading to cytoprotective autophagy and apoptotic death in human head and neck cancer cells

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a major killer worldwide and innovative measures are urgently warranted to lower the morbidity and mortality caused by this malignancy. Aberrant redox and metabolic status in HNSCC cells offer a unique opportunity to specifically target cancer cells. Therefore, we investigated the efficacy of grape seed extract (GSE) to target the redox and bioenergetic alterations in HNSCC cells. GSE treatment decreased the mitochondrial electron transport chain complex III act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
4
14
0
1
Order By: Relevance
“…Earlier reports have shown that GSE causes cell death in human head and neck and bladder carcinoma cells by oxidative stress induction, and since B2G2 is the major active constituent of GSE, we next measured whether B2G2 also induces ROS generation in human PCa LNCaP and 22Rv1 cells using DCFDA as a probe compound. Results showed a robust ROS generation by B2G2 treatment in both LNCaP and 22Rv1 cells (Figures D and E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reports have shown that GSE causes cell death in human head and neck and bladder carcinoma cells by oxidative stress induction, and since B2G2 is the major active constituent of GSE, we next measured whether B2G2 also induces ROS generation in human PCa LNCaP and 22Rv1 cells using DCFDA as a probe compound. Results showed a robust ROS generation by B2G2 treatment in both LNCaP and 22Rv1 cells (Figures D and E).…”
Section: Resultsmentioning
confidence: 99%
“…Along with the failure of several antioxidants, there is plethora of the literature suggesting that elevated intracellular ROS level provides cancer cells an aggressive phenotype; however, ROS levels above a particular threshold could be deleterious to cancer cells . Therefore, recent research efforts have also focused onto increase ROS production in cancer cells via compounds displaying pro‐oxidant properties . Importantly, compared to normal prostate epithelial cells, PCa cells generate higher amounts of ROS making them more prone to ROS‐induced damages; enhanced ROS levels trigger pro‐apoptotic signaling pathways as the anti‐oxidant defense mechanisms are already compromised in these cancer cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex III, also known as cytochrome c reductase, acts similarly to complex I by extracting electrons from ubiquinol to reduce cytochrome c (Denis, 1986; Pramanik et al, 2011). The ability of complexes I and III to act as electron transporters suggests that reduced levels of these complexes may increase generation of oxidative stress from the mitochondria by allowing electrons to leak from the system to react with molecular oxygen, generating ROS (Janssen et al, 2006; Li et al, 2003; Shrotriya et al, 2015). Oxidative damage can disrupt enzymes and transporters, change expression of certain genes or activate inflammation through redox sensors and activate apoptosis (Fariss et al, 2005; Kim et al, 2014; Naoi et al, 2005; Ray et al, 2012; Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway regulates the autophagy via its effector proteins and signalling molecules like mTORC, Bcl‐2, Beclin‐1 and ROS . The kinase mTOR is a critical regulator of autophagy induction, with activated mTOR (Akt and MAPK signaling) suppressing autophagy .…”
Section: Discussionmentioning
confidence: 99%